2011
DOI: 10.1021/ja2093579
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cation Diels–Alder Cycloadditions by Visible Light Photocatalysis

Abstract: Ruthenium(II) polypyridyl complexes promote the efficient radical cation Diels–Alder cycloaddition of electron-rich dienophiles upon irradiation with visible light. These reactions enable facile [4+2] cycloadditions that would be electronically mismatched under thermal conditions. Key to the success of this methodology is the availability of ligand-modified ruthenium complexes that enable the rational tuning of electrochemical properties of the catalyst without significantly perturbing the overall photophysica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
215
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 368 publications
(223 citation statements)
references
References 45 publications
6
215
0
2
Order By: Relevance
“…Specifically, upon oxidation of trans -anethole ( 313 ), radical cation 314 was found to react with isoprene ( 315 ) in a [4 + 2] cycloaddition to provide cyclohexene Diels–Alder adduct 316 (Scheme 68). 163 Although Ru(bpy) 3 2+ is a competent catalyst for this reaction, Yoon and co-workers observed higher efficiencies for the [4 + 2] cycloaddition using the more oxidizing analog Ru(bpz) 3 2+ . In contrast to Ru(bpy) 3 2+ , which must be oxidized to its Ru(bpy) 3 3+ oxidation state before it can oxidize electron-rich styrenes such as trans-anethole ( E 1/2 red = +1.2 V vs SCE), 158 Ru(bpz) 3 2+ is capable of performing this oxidation directly from its photoexcited state ( E 1/2 *II/I = +1.45 V vs SCE 55 for *Ru(bpz) 2+ 3 as compared to E 1/2 *II/I = +0.77 vs SCE 21 for *Ru(bpy) 3 2+ ).…”
Section: Redox Neutral Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, upon oxidation of trans -anethole ( 313 ), radical cation 314 was found to react with isoprene ( 315 ) in a [4 + 2] cycloaddition to provide cyclohexene Diels–Alder adduct 316 (Scheme 68). 163 Although Ru(bpy) 3 2+ is a competent catalyst for this reaction, Yoon and co-workers observed higher efficiencies for the [4 + 2] cycloaddition using the more oxidizing analog Ru(bpz) 3 2+ . In contrast to Ru(bpy) 3 2+ , which must be oxidized to its Ru(bpy) 3 3+ oxidation state before it can oxidize electron-rich styrenes such as trans-anethole ( E 1/2 red = +1.2 V vs SCE), 158 Ru(bpz) 3 2+ is capable of performing this oxidation directly from its photoexcited state ( E 1/2 *II/I = +1.45 V vs SCE 55 for *Ru(bpz) 2+ 3 as compared to E 1/2 *II/I = +0.77 vs SCE 21 for *Ru(bpy) 3 2+ ).…”
Section: Redox Neutral Reactionsmentioning
confidence: 99%
“…163 Exposure of styrene 318 and myrcene ( 319 ) to the photoredox conditions afforded cyclohexene 320 in 80% yield (Scheme 69). Deprotection of the silyl group, oxidation, and amide coupling completed the rapid synthesis of heitziamide A.…”
Section: Redox Neutral Reactionsmentioning
confidence: 99%
“…6B) (63). These reactions provide a valuable alternative to thermal Diels–Alder cycloaddition reactions, which have been applied to the synthesis of complex carbocyclic organic structures for decades.…”
Section: Photogenerated Radical Ionsmentioning
confidence: 99%
“…( A ) Yoon has demonstrated that the photocatalytic activation of enones produces radical anions that readily participate in [2+2] cycloadditions to afford cyclobutane products that are not generated upon UV irradiation (60). ( B ) Likewise, the photooxidation of electron-rich styrenes yields an electron-deficient radical cation that undergoes facile [4+2] cycloaddition with an electron rich diene, a reaction that is disfavored under thermal conditions (63). ( C ) Radical ion intermediates also afford products with atypical atom connectivities, such as the exclusive formation of the less common anti -Markovnikov product under photochemical conditions (64).…”
Section: Figmentioning
confidence: 99%
“…80 Key to this work was the availability of bipyridine ligand analogs that allowed for systematic tuning of the ruthenium photocatalyst to possess a large enough excited state oxidation potential to directly oxidize olefins.…”
mentioning
confidence: 99%